2016
DOI: 10.1073/pnas.1619047114
|View full text |Cite
|
Sign up to set email alerts
|

DNA demethylation is initiated in the central cells of Arabidopsis and rice

Abstract: Cytosine methylation is a DNA modification with important regulatory functions in eukaryotes. In flowering plants, sexual reproduction is accompanied by extensive DNA demethylation, which is required for proper gene expression in the endosperm, a nutritive extraembryonic seed tissue. Endosperm arises from a fusion of a sperm cell carried in the pollen and a female central cell. Endosperm DNA demethylation is observed specifically on the chromosomes inherited from the central cell in Arabidopsis thaliana, rice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
203
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(221 citation statements)
references
References 44 publications
13
203
0
Order By: Relevance
“…5). The semiconservative model of CG methylation inheritance (1), and the considerable genetic evidence in support of this model (31)(32)(33), is more compatible with the higher efficiency of CG methylation in the male germ line (microspores and sperm), and with the similarly high efficiency observed in female plant gametes (34), than with that observed in somatic tissues (28). In heterochromatic TEs, much or all of the increased efficiency might be accounted by reduced levels of histone H1 (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…5). The semiconservative model of CG methylation inheritance (1), and the considerable genetic evidence in support of this model (31)(32)(33), is more compatible with the higher efficiency of CG methylation in the male germ line (microspores and sperm), and with the similarly high efficiency observed in female plant gametes (34), than with that observed in somatic tissues (28). In heterochromatic TEs, much or all of the increased efficiency might be accounted by reduced levels of histone H1 (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Heterosis was observed in a parent-of-origin manner; the reciprocal cross did not result in heterosis (Dapp et al, 2015). This suggests a maternal effect (Park et al, 2016). In our design, we used Col-wt as the female parent and various ddm1-derived epiRILs as the male parent.…”
Section: Discussionmentioning
confidence: 99%
“…The egg cell seems to be the exception, as we observed a significant decrease of signal upon its maturation, which might be due to either demethylation or loss of symmetrical methylation resulting from lack of MET1 activity . The methylome of the egg cell in rice was published recently (Park et al 2016) and revealed a CG methylation pattern typical of somatic cells. Assuming that these results are also valid in the Arabidopsis egg cell, this might suggest significant hemimethylation rather than demethylation in the egg cell.…”
Section: Discussionmentioning
confidence: 99%